Association of serum albumin levels with kidney function decline and incident chronic kidney disease in elders. Issue 6 (23rd August 2017) - Lang, Joshua; Katz, Ronit; Ix, Joachim H; Gutierrez, Orlando M; Peralta, Carmen A; Parikh, Chirag R; Satterfield, Suzanne; Petrovic, Snezana; Devarajan, Prasad; Bennett, Michael; Fried, Linda F; Cummings, Steven R; et al.
ABSTRACT: Background: Previous studies in HIV-infected individuals have demonstrated serum albumin to be strongly associated with kidney function decline, independent of urine albumin and inflammatory markers. Lower serum albumin concentrations may be an under-appreciated risk factor for kidney function decline in elders. Methods: We performed a cohort analysis in the Health Aging and Body Composition Study, a cohort of well-functioning, bi-racial, community-dwelling elders between the age of 70 and 79 years. We examined the associations of serum albumin concentration with longitudinal kidney function decline by estimated glomerular filtration rate (eGFR). Outcomes included linear eGFR decline, rapid kidney function decline defined as >30% decrease in eGFR, defined as a final eGFR <60 mL/min/1.73 m 2 in those with an eGFR >60 mL/min/1.73 m 2 at baseline. Cystatin C-based eGFR was calculated at baseline, Year 3 and Year 10. Results: Mean age was 74 years, and mean eGFR was 73 mL/min/1.73 m 2 at baseline. The mean rate of eGFR change was 1.81 mL/min/1.73 m 2 per year. After multivariate adjustment, lower serum albumin concentrations were strongly and independently associated with kidney function decline (−0.11 mL/min/1.73 m 2 per year for each standard deviation decrease serum albumin; −0.01 to − 0.20) with no attenuation after adjustment for urine albumin and inflammatory markers (−0.12, −0.03 to − 0.22). When divided into quartiles, serum albumin levels ≤3.80 g/dL were associated with increased odds of rapid kidney function decline (odds ratio 1.59; 1.12–2.26) and increased risk of incident chronic kidney disease (incident rate ratio 1.29; 1.03–1.62) relative to levels >4.21g/dL. Urine albumin to creatinine ratio (ACR) was also significantly and independently associated with kidney function decline (−0.08 mL/min/1.73 m 2 per year for urine ACR >30 mg/g; −0.82 to − 0.13). Conclusions: Lower serum albumin levels are strongly and independently associated with kidney function decline in elders, independent of clinical risk factors, urine albumin and measured inflammatory markers.